Kontestasi Hukum Musik Perspektif Islam (Studi Analisis Gagasan Seni Tauhid Ismail Raji al-Faruqi) - Muhamad A'thoillah Mubarok; Mira Wardhani; Yushi Mahabbatun Nafsi (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat (LP3M) Institut Agama Islam Bakti Negara (IBN) Tegal, 2025)
The polemic of music and song law is again crowded on social media, starting from the translation of surat as-Syuara as a letter of poets who were identified with musicians by one of the preachers who eventually received various comments on social media. Departing from this problem, the author will reveal how Islma'il Raji al-Faruqi's views on music, a figure known for the idea of monotheistic art. This writing attempts to explain the expression of Islamic art offered by Ismail Raji al-Faruqi. This study focuses on monotheism as the main objective of the Islamic worldview. The method used in this writing uses library research. The type of data used by the author uses literature-based data, in the form of primary and secondary data. The approach used in this writing uses a thematic method. The formulation of the underlying problem of this writing is expected to answer the question of music polemic as an expression of Islamic art according to Ismail Raji al-Faruqi. The idea of monotheism is an expression of the objective, transcendent, mystical, and inexpressible values of beauty, as well as the idea of beauty that is subjective, expressive, and culturally comprehensible. Al-Faruqi's thinking shows that literary art, calligraphy, ornamentation, sound art, and room art cannot be separated from monotheism as a worldview in Islam.